2021
DOI: 10.1136/bmjopen-2020-042062
|View full text |Cite
|
Sign up to set email alerts
|

Automated mechanical cardiopulmonary resuscitation devices versus manual chest compressions in the treatment of cardiac arrest: protocol of a systematic review and meta-analysis comparing machine to human

Abstract: IntroductionCardiac arrest is a leading cause of death in industrialised countries. Cardiopulmonary resuscitation (CPR) guidelines follow the principles of closed chest compression as described for the first time in 1960. Mechanical CPR devices are designed to improve chest compression quality, thus considering the improvement of resuscitation outcomes. This protocol outlines a systematic review and meta-analysis methodology to assess trials investigating the therapeutic effect of automated mechanical CPR devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…While some studies have reported favorable outcomes with mechanical chest compressions in selected patients (1)(7)(8), the current American Heart Association (AHA) Guidelines for Cardiopulmonary Resuscitation (CPR) 2020 do not endorse the routine use of mechanical chest compressions based on considerations of quality, safety, feasibility, and practicality (9). However, the guidelines do not provide speci c recommendations on when to use mechanical CPR, such as in which patient populations, under what circumstances, or at what stage of resuscitation (9)(10) (11). In addition, the comparative effectiveness of mechanical versus manual chest compressions remains unclear (4)(9)(10) (12).…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have reported favorable outcomes with mechanical chest compressions in selected patients (1)(7)(8), the current American Heart Association (AHA) Guidelines for Cardiopulmonary Resuscitation (CPR) 2020 do not endorse the routine use of mechanical chest compressions based on considerations of quality, safety, feasibility, and practicality (9). However, the guidelines do not provide speci c recommendations on when to use mechanical CPR, such as in which patient populations, under what circumstances, or at what stage of resuscitation (9)(10) (11). In addition, the comparative effectiveness of mechanical versus manual chest compressions remains unclear (4)(9)(10) (12).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that A-CPR was superior to M-CPR. 8 , 17 , 19 However, a meta-analysis of nine prospective studies has suggested that mechanical CPR was inferior to manual CPR in terms of attaining ROSC, and no differences in survival to discharge for in-hospital cardiac arrest patients. 11 Khan et al also reported that manual CPR is more effective in improving hospital discharge or survival at 30 days compared with mechanical CPR.…”
Section: Discussionmentioning
confidence: 99%
“…A-CPR allows adjustment of depth, frequency and proportion of external chest compression according to the specific situation of the patient, and provides constant and lasting ventilation support and external chest compression. 8 Over the past years, numbers of studies have investigated the effectiveness of A-CPR and M-CPR in OHCA patients 9,10,11 , but few in IHCA patients. Therefore, we performed an observational study to analyze the efficacy of A-CPR and M-CPR in the rescue of cardiac and respiratory arrest by comparing their rescue effect, blood gas analysis index and respiratory dynamics, and condition improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, providing high-quality CPR has been proven to be insufficient in a variety of contexts, particularly among community members. This is concerning since CPR is intrinsically inefficient, producing just a third of normal cardiac blood flow and cerebral blood flow when performed according to standards (52). Qualified rescuers must perform high-quality CPR to improve the chances of restoring spontaneous circulation.…”
Section: The Performance Of Cpr -Factors To Survival Of Victimsmentioning
confidence: 99%